Defining The Boundary Of Regions In Thematic Map Using Flexible Ellipse Shape Region - Taib, Mohd Hafiz; Miskon, Muhammad Fahmi; Sakidin, Hamzah; Sha’abani, Mohd Nurul Al-Hafiz (AENSI Publisher, 2014)
-